Microstructural characteristics and mechanical behaviour of aluminium matrix composites reinforced with Si-based refractory compounds derived from rice husk. Issue 1 (1st January 2021) - Adediran, Adeolu Adesoji; Alaneme, Kenneth Kanayo; Oladele, Isiaka Oluwole; Akinlabi, Esther Titilayo
Abstract: The microstructural characteristics and mechanical behaviour of aluminium matrix composites reinforced with Si-based refractory compounds (SRC) derived from rice husk were investigated. The reinforcement materials (SRC) were synthesized using a carbothermal processing technique. The reinforcement was used to prepare a 10 wt.% Al-Mg-Si alloy-based composite using a double stir casting process. The composites produced were characterized using microhardness, tensile properties, scanning electron microscopy (SEM), and X-ray diffractometer (XRD). From the results, A1650, C1650, and A1600 grades of the samples show more resistance to indentation due to the high proportion of hard SRC in the reinforced materials. Superior elongation values were observed for these composites A1650, C1650 and A1600 grades, respectively. The grades A1250, B1250, and C1250 series had the least toughness values within the range of 20–37% as compared to the control sample. For all composites under examination, the percent porosity was noted to be less than 4% and the strain to fracture was within 24–38%. Higher intensity of SiC was observed from the XRD spectrum and the formation of intermetallic materials. The tensile fracture surface morphologies of the composites produced were similar, showing a ductile dimple-like structure. The formation of a micro-crack and micro-void was also observed along the interphase.